2001
DOI: 10.1128/aem.67.10.4752-4759.2001
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Geotrichum candidum Strains Isolated from Traditional Cheesemaking Fabrications in France

Abstract: The diversity of French fungus-ripened cheeses is due partly to the succession of fungi that colonize the cheese during ripening. Geotrichum candidum appears in the early stages of ripening on soft cheeses such as Camembert and semihard cheeses such as St. Nectaire and Reblochon. Its lipases and proteases promote flavor development, and its aminopeptidases reduce bitterness imparted by low-molecular-weight peptides in cheese. We assessed the genetic diversity of G. candidum strains by using random amplificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 37 publications
1
74
1
3
Order By: Relevance
“…When the fungus grows on the cheese surface, the white coat formation can be observed. In cheese, the overgrowth of fungus is responsible not only for changing the appearance but also for the catabolism of milk protein and fat (Marcellino et al 2001). In the dairy practice, it is important to keep the growth of G. candidum under the desired level and to control in this way the flavour development.…”
mentioning
confidence: 99%
“…When the fungus grows on the cheese surface, the white coat formation can be observed. In cheese, the overgrowth of fungus is responsible not only for changing the appearance but also for the catabolism of milk protein and fat (Marcellino et al 2001). In the dairy practice, it is important to keep the growth of G. candidum under the desired level and to control in this way the flavour development.…”
mentioning
confidence: 99%
“…A role of G. candidum in food could be evaluated posi-tive but also negative. It is widely used in a milk industry as a second/adjunct culture in many soft cheeses such as Camembert, semi-fresh and semihard cheeses (Addis et al 2001;Marcellino et al 2001;Boutrou & Guéguen 2005;Pottier et al 2008). The metabolic activity of G. candidum plays an important role in the development of characteristic flavours, taste and other qualities of milk products (Marcellino et al 2001).…”
mentioning
confidence: 99%
“…The yeast Geotrichum candidum which was identified in our study is appearing in the early stages of ripening on soft and semi-hard French cheeses. Its lipases and proteases promote flavor development, and its aminopeptidases reduce bitterness imparted by lowmolecular-weight peptides in cheese (Marcellino et al, 2001). Njage et al (2011) also identified species belonging to the genera Rhodotorula, Cryptococcus, Candida, Trichosporon, Geotrichum and Issatchenkia which weren't founded in our study.…”
Section: Resultsmentioning
confidence: 66%